The Impact of Cutting with a Shearer on the Conditions of Longwall Ventilation - Wacław Dziurzyński (MDPI AG, 2021)
In coal mines that are exploiting methane-saturated seams, high-level emission of methane is often the basic limitation for modern and high-efficiency longwall complexes. This paper presents selected observations and tests carried out in the Cw-4 longwall in seam 364/2 of the Budryk mine, which belongs to JSW SA. To observe the methane levels in the Cw-4 longwall, additional sensors were installed at the end section of the longwall from the side of the gobs, and the air velocity and methane concentration were registered in a multi-point system that were built in the selected longwall cross-section. The air parameters were recorded in the monitoring system. The use of multi-point simultaneous measurements of the local velocities and concentrations of methane in the longwall cross-section allowed for the precise determination of the air and methane volume flow using the velocity field method. This allowed us to perform a comparative analysis of the obtained records of the air parameters using special software to determine the distribution of the parameters in the cross-section of the excavation. An important element of the study was the simultaneous registration of the methane concentration in the longwall, information on the operating times, the direction of shearer operation, and the type of work being done (i.e., mining/cleaning).